2011
DOI: 10.1186/1472-6750-11-101
|View full text |Cite
|
Sign up to set email alerts
|

New biotechnological perspectives of a NADH oxidase variant from Thermus thermophilus HB27 as NAD+-recycling enzyme

Abstract: BackgroundThe number of biotransformations that use nicotinamide recycling systems is exponentially growing. For this reason one of the current challenges in biocatalysis is to develop and optimize more simple and efficient cofactor recycling systems. One promising approach to regenerate NAD+ pools is the use of NADH-oxidases that reduce oxygen to hydrogen peroxide while oxidizing NADH to NAD+. This class of enzymes may be applied to asymmetric reduction of prochiral substrates in order to obtain enantiopure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 67 publications
2
81
0
Order By: Relevance
“…[27] Likewise, we have already reported that multipoint covalent immobilization and crosslinking through aldehyde chemistry stabilizes both NOX and CAT. [32,33] Therefore, the immobilization of such a trienzyme system on Ag-AG minimizes product inhibition and maximizes protein stability. On one hand, as GlyDH, NOX, and CAT are multimers, their post-immobilization covalent crosslinking avoids subunit dissociation, which stabilizes their quaternary structures.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Likewise, we have already reported that multipoint covalent immobilization and crosslinking through aldehyde chemistry stabilizes both NOX and CAT. [32,33] Therefore, the immobilization of such a trienzyme system on Ag-AG minimizes product inhibition and maximizes protein stability. On one hand, as GlyDH, NOX, and CAT are multimers, their post-immobilization covalent crosslinking avoids subunit dissociation, which stabilizes their quaternary structures.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the role of C. glutamicum cells in metabolite overproduction and the importance of cofactor regeneration such as NAD + /NADH cycling in metabolic engineering (Hou et al 2014;Ji et al 2013;Rocha-Martin et al 2011;Zhang et al 2014), the noxA gene may be of importance in the field of biotechnology. Toward fully elucidating the function of noxA in C. glutamicum physiology, additional investigations are underway.…”
Section: Discussionmentioning
confidence: 99%
“…The flavoprotein catalysts tested were miniSOG (mini singlet oxygen generator),26 NOX (NADH oxidase from Thermus thermophilus ),27 GOX (glucose oxidase from Aspergillus niger ),28 and GR (glutathione reductase from S. cerevisiae ) 29. MiniSOG is a flavin mononucleotide (FMN) containing small protein investigated as a genetically encodable photosensitizer for the selective generation of singlet O 2 30, 31, 32.…”
mentioning
confidence: 99%
“…The bacterial NOX enzyme generates hydrogen peroxide (H 2 O 2 ) from O 2 by oxidizing NADH while the eukaryotic GOX naturally oxidizes glucose to H 2 O 2 and d ‐glucono‐δ‐lactone. NOX and GOX have both been widely exploited in biocatalysis 27, 33. GR is a NADPH‐dependent oxidoreductase exerting a central role in glutathione metabolism for most aerobic organisms 34.…”
mentioning
confidence: 99%
See 1 more Smart Citation